Improved Thermally Activated Building System Design Method Considering Integration of Air Systems. (27th June 2018) - Chung, Woong June; Lim, Jae-Han
Abstract : The purpose of the thermally activated building system design is to maintain the thermal comfort of the building indoor environment by securing enough thermal output of the system. For preventing the condensation on the thermally activated building system, the air system is mostly integrated with the thermally activated building system. However, the common design method in the standards only considers the thermal performance of the system itself and cannot reflect the effects of the air system. Thus, the design process of the thermally activated building system should include the consideration about the latent load and ventilation. In order to reflect the effect of the air system, the amount of sensible load removed by the thermally activated building system and air system should be included in the design process. The sensible load handled by the air system highly depends on the type of the air system and design consideration to prevent the condensation and maintain the indoor air quality. In this study, the air system choosing process was included by simulating and observing the sensible load removed by different types of the air system, and thermal performance adjustment in the design process was proposed.